A measure of informed choice - Marteau, Theresa M. (Health Expect, 2001)
Objective To develop a measure of informed choice. Conceptualization and measurement The measure is based on the following definition of an informed choice: one that is based on relevant knowledge, consistent with the decision‐maker’s values and behaviourally implemented. The measure comprises an eight‐item scale of knowledge, a four‐item scale assessing attitudes towards undergoing the screening test and a record of test uptake. Participants Sixty‐six women awaiting their first antenatal clinic appointments. Measure development In women offered a screening test in pregnancy, the internal reliability of both the knowledge and the attitude scales was acceptable (alpha coefficients 0.82 and 0.83, respectively). Of the 42 women completing both scales, 18 were classified as having made an informed choice, and 24 were classified as having made an uninformed choice. Conclusion The results of this preliminary study provide some evidence to support the feasibility of conceptualizing and measuring informed choices regarding screening using a brief measure assessing knowledge and attitudes. The validity and utility of this approach awaits further studies, involving larger numbers of participants, offered different screening tests.